Neurosurgery rounds questions and answers - Shaya, Mark R. (Thieme, 2011)
"Neurosurgery Rounds: Questions and Answers is the first guide dedicated to preparing residents and medical students for the challenging questions -- known as "pimping" in the vernacular -- they will frequently encounter on neurosurgery rotation. Nine succinct chapters fully cover the basic and clinical neurosciences in a convenient Q&A format that is ideal for self-study. Short answers and explanations appear directly below the questions to enable easy reading on the go. Features - Over 1,600 questions and answers quiz readers on a wide range of neurosurgical topics - 30 cases -- also in an accessible Q&A format -- prime readers for clinical situations - More than 150 high-quality radiographs and anatomy drawings supplement the text The perfect size to fit in a lab coat pocket, this concise review will be the constant companion of every medical student on a neurosurgical rotation and every neurosurgery resident or general surgery resident who needs to prepare for rounds or study for board examinations"--Provided by publisher.